Curricula components for entrustable professional activities for the subspecialty of pediatric cardiology. (March 2017) - Srivastava, Shubhika; Braunlin, Elizabeth; Brown, David; Cabrera, Antonio G.; Frank, Lowell; Glickstein, Julie S.; Johnston, Troy; Koenig, Peter; McDaniel, George; Printz, Beth; Reinking, Benjamin; Wong, Pierre; et al.
Highlights: Entrustable professional activities define the tasks, knowledge and skills expected of a physician. II The training guidelines define the curriculum and training environment. Curricula components define knowledge, skills and scope of practice.